2012
DOI: 10.1080/00221309.2011.652236
|View full text |Cite
|
Sign up to set email alerts
|

Altering Participants’ Hypothetical Annual Income Can Alter Their Rates of Discounting the Same Delayed Monetary Outcome

Abstract: Delay discounting occurs when the subjective value of an outcome decreases because its delivery is delayed. Past research has shown that how steeply participants discount an outcome varies inversely with the value of previously discounted outcomes. In the present study, participants discounted the same hypothetical monetary outcome ($1,000) after their hypothetical annual income was halved (Experiment 1) or doubled (Experiment 2). Rates of discounting decreased and increased, respectively, after these manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…In delay discounting, a positive transition may increase self‐controlled choices, whereas a negative transition may result in impatience. This is consistent with previous findings that participants who received a narrative indicating a financial loss showed steeper discounting (Bickel et al, 2016; Mellis et al, 2018; Sze et al, 2017; Weatherly, 2012). One possible reason for the discrepant findings of Weatherly (2012) may be the degree of the economic shift.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In delay discounting, a positive transition may increase self‐controlled choices, whereas a negative transition may result in impatience. This is consistent with previous findings that participants who received a narrative indicating a financial loss showed steeper discounting (Bickel et al, 2016; Mellis et al, 2018; Sze et al, 2017; Weatherly, 2012). One possible reason for the discrepant findings of Weatherly (2012) may be the degree of the economic shift.…”
Section: Discussionsupporting
confidence: 92%
“…One possible reason for the different results is the different ratios of outcome magnitude to economic context among the studies. In both studies, the outcome magnitude was $1,000; however, the change in economic context varied across studies, being unspecified in some studies (Bickel et al, 2016; Mellis et al, 2018; Sze et al, 2017) and a $50,000 change in one study (Weatherly, 2012).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Individuals with lower incomes are also more likely to engage in behaviors associated with higher DD (e.g., problem drinking and cigarette use; Bickel et al, 2014). Previous studies have shown that negative income shock simulations (i.e., abrupt transitions to poverty) can increase rates of DD (Sze, Stein, Bickel, Paluch, & Epstein, 2017;Weatherly, 2012) and that EFT can reduce the impact of negative income shock (Sze et al, 2017). However, simulations of negative income shock may be different than chronic experiences of poverty.…”
Section: Introductionmentioning
confidence: 99%
“…One can manipulate people’s hypothetical incomes (Weatherly, 2012), but another approach to this issue would be to use an animal model and manipulate level of deprivation directly. Past research with animal models investigating the relation between deprivation and delay to different rewards has yielded inconsistent results.…”
mentioning
confidence: 99%